The extracellular matrix: Structure, composition, age-related differences, tools for analysis and applications for tissue engineering. (20th December 2014) - Kular, Jaspreet K; Basu, Shouvik; Sharma, Ram I
The extracellular matrix is a structural support network made up of diverse proteins, sugars and other components. It influences a wide number of cellular processes including migration, wound healing and differentiation, all of which is of particular interest to researchers in the field of tissue engineering. Understanding the composition and structure of the extracellular matrix will aid in exploring the ways the extracellular matrix can be utilised in tissue engineering applications especially as a scaffold. This review summarises the current knowledge of the composition, structure and functions of the extracellular matrix and introduces the effect of ageing on extracellular matrix remodelling and its contribution to cellular functions. Additionally, the current analytical technologies to study the extracellular matrix and extracellular matrix–related cellular processes are also reviewed.